Visualizing the autonomic and somatic innervation of the female pelvis with 3D MR neurography: a feasibility study. (December 2020) - De Paepe, Katja N; Higgins, David M; Ball, Iain; Morgan, Veronica A; Barton, Desmond P; deSouza, Nandita M
Background: Treatment of female pelvic malignancies often causes pelvic nerve damage. Magnetic resonance (MR) neurography mapping the female pelvic innervation could aid in treatment planning. Purpose: To depict female autonomic and somatic pelvic innervation using a modified 3D NerveVIEW sequence. Material and Methods: Prospective study in 20 female volunteers (n = 6 normal, n = 14 cervical pathology) who underwent a modified 3D short TI inversion recovery (STIR) turbo spin-echo (TSE) scan with a motion-sensitive driven equilibrium (MSDE) preparation radiofrequency pulse and flow compensation. Modifications included offset independent trapezoid (OIT) pulses for inversion and MSDE refocusing. Maximum intensity projections (MIP) were evaluated by two observers (Observer 1, Observer 2); image quality was scored as 2 = high, 1 = medium, or 0 = low with the sciatic nerve serving as a reference. Conspicuity of autonomic superior (SHP) and bilateral inferior hypogastric plexuses (IHP), hypogastric nerves, and somatic pelvic nerves (sciatic, pudendal) was scored as 2 = well-defined, 1 = poorly defined, or 0 = not seen, and inter-observer agreement was determined. Results: Images were of medium to high quality according to both observers agreeing in 15/20 (75%) of individuals. SHP and bilateral hypogastric nerves were seen in 30/60 (50%) of cases by both observers. Bilateral IHP was seen in 85% (34/40) by Observer 1 and in 75% (30/40) by Observer 2. Sciatic nerves were well identified in all cases, while pudendal nerves were seen bilaterally by Observer 1 in 65% (26/40) and by Observer 2 in 72.5% (29/40). Agreement between observers for scoring nerve conspicuity was in the range of 60%–100%. Conclusion: Modified 3D NerveVIEW renders high-quality images of the female autonomic and pudendal nerves.